Peran Orang Tua dalam Mendampingi Anak Usia Sekolah Dasar dalam Menggunakan Teknologi Digital: Kajian Pengabdian Masyarakat - Aswidani (Ambacang: Jurnal Inovasi Pengabdian Masyarakat, 2026)
The development of digital technology has brought significant changes to the lives of elementary school children. Children aged 6–12 years are increasingly intensive in using digital devices for both learning and entertainment. This condition requires parental guidance to ensure that technology use does not lead to negative impacts such as gadget addiction, exposure to age-inappropriate content, and socio-emotional disturbances. This community service activity aims to enhance the understanding of parents and university students regarding the concept of digital parenting and strategies for assisting children in the use of digital devices. The implementation method involved an interactive socialization session lasting three hours with 25 participants, consisting of parents and students. The activities included material delivery, group discussions, and simulations of drafting a Family Media Agreement. The results showed an increase in parents’ knowledge of digital literacy, their ability to establish family rules related to gadget use, and their awareness of the importance of open communication with children. The presence of students as facilitators also strengthened academic–community collaboration in fostering a culture of digital literacy. The conclusion of this activity is that digital literacy socialization is effective in improving parents’ capacity to guide children in using digital devices in a healthy and productive manner. Recommendations for future activities include the development of digital parenting modules and the integration of family digital literacy programs with schools and local communities.